Investigating Late Chalcolithic Period settlement on the Marivan Plain, western Iran. First insights from the Marivan Plain Survey project - Zamani Dadane, Morteza; Mohammadi Ghasrian, Sirvan; Bruun Skuldbøl, Tim Boaz (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
The Marivan Plain Survey project is undertaking a review of previous survey work in the region of Marivan, which lies in the province of Kurdistan, western Iran. This paper presents the first results from this new survey project. During the summer of 2018 it recorded significant new evidence for the development of Late Chalcolithic period settlement and provided new insights into cultural interaction with the southern Mesopotamian Uruk culture.